The Topicality of Phenomenology? (Nóema, 2012)
Is it possible to speak of a “topicality” of phenomenology and, in particular, of Husserl’s phenomenology? In the last decades, as a matter of fact, a “strange” trajectory has led to its peculiar “comeback”. In a post-Heideggerian horizon, phenomenology offers to philosophy the possibility not to dismiss its rigour, to interact positively with scientific researches, to call into question metaphysical and scientifical all-encompassing explanations, drawing on a methodological adherence to the manifestation.
Keywords: Occident; Deconstruction; Experience; Method; Manifestation